Modified atmosphere affects glucosinolate metabolism during postharvest storage of broccoli - CASAJÚS, Victoria; HOWE, Kevin; FISH, Tara; CIVELLO, Pedro; THANNHAUSER, Theodore; LI, Li; LOBATO, María Gómez; MARTINEZ, Gustavo (Food Science and Technology, 2024)
Broccoli is a vegetable with a growing consumer demand worldwide due to its important nutritional properties, including high amounts of glucosinolates. However, this vegetable has a short postharvest life and quickly loses its organoleptic and nutritional quality. Modified atmosphere is one of the numerous methodologies used to delay deterioration during postharvest storage of broccoli heads. In this study, the effect of a modified atmosphere during postharvest storage of broccoli on glucosinolate metabolism was evaluated. Five glucosinolates were identified by using a UPLC system coupled to a mass spectrometer. We detected one aliphatic glucosinolate and four indolic glucosinolates, and their concentration was found to decrease during storage. The decrease in content was less marked, and in some cases, an increased level was observed in the treated samples. Moreover, the treatment made it possible to maintain higher expression (analyzed by real-time quantitative PCR) of genes linked to glucosinolate biosynthesis. We also detected an increased expression of some genes related to indolic glucosinolate biosynthesis. Overall, storage of broccoli in modified atmospheres allowed for maintaining better visual quality and higher levels of glucosinolates.